Boosted large-scale production and purification of a thermostable archaeal phosphotriesterase-like lactonase for organophosphate decontamination. (1st March 2017) - Restaino, Odile Francesca; Borzacchiello, Maria Giovanna; Scognamiglio, Ilaria; Porzio, Elena; Manco, Giuseppe; Fedele, Luigi; Donatiello, Cinzia; De Rosa, Mario; Schiraldi, Chiara
Abstract: Thermostable phosphotriesterase-like lactonases (PLLs) from extremophile archaea, like Sso Pox from Sulfolobus solfataricus, are attractive biotechnological tools with industrial applications as organophosphate decontaminants, but their manufacturing still remains an unresolved issue because of the high costs and the low production yields. In this paper, for the first time, an efficient biotechnological process for the production and purification of a recombinant, engineered PLL, Sso Pox W263F, expressed in E. coli, has been set up by studying new induction strategies, by designing high cell density cultivations and a new membrane-based downstream process. In fed batches, the enzyme production was boosted of 69-fold up to 4660.0 U L −1 using galactose as inducer in the replacement of IPTG; the process was scalable from 2.5 up to 150 L. By coupling a single thermo-precipitation step and an ultrafiltration process, a total enzyme recovery of 77% with a purity grade of almost 80% was reached.